2020
DOI: 10.1002/14651858.cd009958.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning for pressure injury prevention in adults

Abstract: 6. Art. No.: CD009958. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 47 publications
1
78
2
12
Order By: Relevance
“…Likewise, within intensive care, Manzano et al 67 found no difference in PI incidence between 2‐hourly and 4‐hourly repositioning on an alternating pressure air mattress. While 2‐hourly repositioning has been acknowledged as the standard of care, 68 wide study variations in repositioning frequency and mattress combinations, with conflicting results, means that optimal repositioning frequency remains unknown 69 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, within intensive care, Manzano et al 67 found no difference in PI incidence between 2‐hourly and 4‐hourly repositioning on an alternating pressure air mattress. While 2‐hourly repositioning has been acknowledged as the standard of care, 68 wide study variations in repositioning frequency and mattress combinations, with conflicting results, means that optimal repositioning frequency remains unknown 69 …”
Section: Discussionmentioning
confidence: 99%
“…While 2-hourly repositioning has been acknowledged as the standard of care, 68 wide study variations in repositioning frequency and mattress combinations, with conflicting results, means that optimal repositioning frequency remains unknown. 69 While the evidence surrounding repositioning is conflicting, repositioning itself has a strong theoretical justification. 68,69 Generally, PI occurs due to unrelieved pressure forces on body tissues, such as tissue between a bony prominence and a mattress surface; 60,70 however, repositioning the body to relieve that pressure subsequently relieves the PI development forces on the affected tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3 Pressure injury has become a significant health issue because of its high cost of treatment, debilitating effect on the patients, and the high recurrence rate despite the preventive measures and treatment. 4,5,6 Pressure injury affects 2.5 million individuals resulting in 60,000 deaths in the US and impacts 700,000 individuals with 29,000 deaths in the UK. 5 The cost of pressure injury care in the UK was estimated at between £1.4 billion and £2.1 billion annually and 9.1 to 11.6 billion dollars annually in the US.…”
Section: Introductionmentioning
confidence: 99%